2019
DOI: 10.1039/c8pp00507a
|View full text |Cite
|
Sign up to set email alerts
|

Photocyclization of diarylethenes: the effect of imidazole on the oxidative photodegradation process

Abstract: It was found that imidazole prevents the side process of diarylethenes photocyclization and the photodegradation of photochromic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…We have previously found that amines, including DABCO, facilitate the photorearrangement of DAEs . In this cyclization, the use of DABCO also resulted in a significant increase in the yields of photoproducts 2a and 2b to reach a quantitative value for 2a .…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…We have previously found that amines, including DABCO, facilitate the photorearrangement of DAEs . In this cyclization, the use of DABCO also resulted in a significant increase in the yields of photoproducts 2a and 2b to reach a quantitative value for 2a .…”
Section: Resultsmentioning
confidence: 73%
“…We have previously found that amines, including DABCO, facilitate the photorearrangement of DAEs. 39 In this cyclization, the use of DABCO also resulted in a significant increase in the yields of photoproducts 2a and 2b to reach a quantitative value for 2a. The high yields are possibly associated with both the facilitation of proton abstraction upon cyclization at an unsubstituted carbon atom and with the reversibility of the process upon photocyclization at a halogensubstituted position (Scheme 3).…”
Section: ■ Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, if the reaction is carried out in chloroform in the presence of DABCO, then the radical process is greatly slowed down and after 2 h of irradiation, the yield of 7 is 71% vs 20% for naphthothiophene 8 (entry 12 in Table ). Based on our recent studies , and these results, it can be assumed that DABCO plays a dual role in these processes. The first of them is to facilitate the deprotonation process and the second is to suppress photochemical oxidative processes.…”
Section: Resultsmentioning
confidence: 79%
“…In particular, the diarylethene triplet was detected in a study of the photoinduced rearrangement of diarylethene 37c . It was shown that upon irradiation of diarylethenes 37c and 56a the cycloaddition of oxazole substituents with photogenerated singlet oxygen is possible . This undesired process can be bypassed under aerobic conditions by using N- methylpyrrolidone as the solvent or by using amines such as DABCO or imidazole as singlet oxygen quenchers .…”
Section: Mechanism Of Photoinduced Rearrangementmentioning
confidence: 99%